Investigation on the use of blue and yellow light-emitting diodes (LEDs) for growth, proximate composition enhancement and morphology of marine microalga Isochrysis sp. - Suhaimi, Norhayati (2016)
Microalgae are photoautotrophic organisms that need light as their main energy source. In this study, the growth, proximate composition and morphology of marine microalga, Isochrysis sp., cultured under blue and yellow light-emitting diodes (LED) with fluorescent light as control were compared. Growth of the microalga was observed for 13 days and the effect of the three different light sources on cell count, optical density and specific growth rate were determined. At the end of the experiment, results showed that Isochrysis sp. cultured under fluorescent light had highest specific growth rate (SGR)while yellow LED and blue LED cultures had similar SGR. Yellow LED and fluorescent light produced higher cell density in culturing Isochrysissp. The cultures were harvested during the stationary phase and proximate analysis was done. Lipid content was significantly higher in Isochrysis sp. grown under yellow LED, whereas, protein composition was significantly higher in blue and yellow LED cultures. Yellow LED and fluorescent light cultures also had significantly high carbohydrate composition compared to blue LED cultures. Cell morphology was studied under scanning electron microscope during initial and final stage of the microalga cultures and fluorescent light produced the largest cells. Thus, it can be concluded that yellow LED had the optimum wavelength for Isochrysis sp. culture. Besides that, different wavelength of lights also affected the morphology of the microalga cells.